Composite positive electrode material, preparation method thereof and sodium ion battery

By optimizing the process conditions of yttrium-doped NFPP and spray-drying method to prepare nanoparticle precursors, the problems of low conductivity and poor rate performance of NFPP positive electrode materials are solved, and the low-cost development of high-performance sodium ion battery positive electrode materials are achieved.

CN119528103AActive Publication Date: 2025-02-28GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411635680.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-28
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The intrinsic electronic conductivity of NFPP cathode materials is low and the rate performance is poor, which affects its electrochemical performance and application development.

Method used

By optimizing the process conditions of yttrium doped NFPP, the nanoparticle precursor was prepared by spray drying, and high-temperature solid phase sintering was performed under an inert gas atmosphere to prepare NFPP-Y composite positive electrode material.

Benefits of technology

The electrochemical performance of NFPP cathode materials is improved, its conductivity and rate performance is enhanced, and a low-cost development path for high-performance sodium ion battery cathode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528103A_ABST
    Figure CN119528103A_ABST
Patent Text Reader

Abstract

The invention is applicable to the technical field of materials, and provides a composite positive electrode material, a preparation method thereof and a sodium ion battery, and the preparation method comprises the following steps: adding specific yttrium salt and water into Na4P2O7, Fe (NO3) 3.9 H2O and NH4H2PO4, and uniformly mixing; the molar ratio of Y < 3 + > to P2O74 <-> is (0.05-0.2): 1; and carrying out spray drying on the mixed solution, and heating the obtained powder precursor to 500-580 DEG C in an inert gas atmosphere at a heating rate of 2-5 DEG C / min for sintering treatment. The preparation method is simple to operate, low in preparation cost, high in production capacity and high in product quality, the composite material precursor composed of nano particles is prepared by optimizing the yttrium-doped NFPP condition and combining spray drying, carbonization is completed by optimizing the high-temperature solid-phase sintering condition, and the obtained composite positive electrode material has excellent electrochemical performance and is suitable for industrial production. And a new way is provided for low-cost development of a high-performance sodium ion battery positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of material technology, and in particular relates to a composite positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] As an emerging electrochemical energy storage technology, sodium-ion batteries have shown great development potential in the field of large-scale electrochemical energy storage due to their abundant resources, low price, and high safety. In the research and development of sodium-ion batteries, the selection of cathode materials is crucial because they directly affect the energy density, cycle stability, and cost-effectiveness of the battery. Sodium iron pyrophosphate (Na4Fe3(PO4)2P2O7, abbreviated as NFPP) is a promising cathode material because it combines the advantages of iron-based phosphates and pyrophosphates, such as high theoretical specific capacity (129 mAh g -1 ), high average operating voltage (3.1V), small volume change (less than 4%), as well as low cost and environmental friendliness.

[0003] However, due to the large anion skeleton of NFPP, its intrinsic electronic conductivity is low and its rate performance is poor, which affects its electrochemical performance and application development. In order to further improve the performance of NFPP, researchers have adopted a variety of modification strategies, such as structural nano-sizing and various carbon material composites or surface carbon coatings. Studies have shown that although the design of suitable carbon composites or carbon coating materials can effectively improve the conductivity of the material surface, giving it high rate performance and good cycle stability, the inherent properties of the material itself will not change. Summary of the invention

[0004] The purpose of the embodiments of the present application is to provide a method for preparing a composite positive electrode material, aiming to solve the problem that the existing NFPP positive electrode material has low intrinsic electronic conductivity and poor rate performance, which leads to limited electrochemical performance and application development.

[0005] The embodiment of the present application is implemented as follows: a method for preparing a composite positive electrode material comprises:

[0006] According to the chemical formula Na4Fe3(PO4)2(P2O7), Na, Fe, PO4 3- and P2O7 4- The molar ratio of Na4P2O7, Fe(NO3)3·9H2O and NH4H2PO4 were weighed respectively, and yttrium salt and deionized water were added and mixed uniformly to obtain a mixed solution; wherein Y 3+ With P2O7 4- The molar ratio is (0.05-0.2):1; the yttrium salt is one of Y(NO3)3, Y2(CO3)3, Y2(SO4)3 and YCl3;

[0007] The mixed solution is ground and then spray-dried to form a dry powder precursor;

[0008] The powder precursor is ground and then heated to 500-580° C. at a heating rate of 2-5° C. / min in an inert gas atmosphere for sintering to obtain a composite positive electrode material.

[0009] The embodiment of the present application also provides a composite positive electrode material, and the composite positive electrode material is prepared by the above-mentioned method for preparing the composite positive electrode material.

[0010] An embodiment of the present application also provides a sodium ion battery, which includes the above-mentioned composite positive electrode material.

[0011] The embodiment of the present application provides a method for preparing a composite positive electrode material, which is simple to operate, has low preparation cost, large production capacity and high product quality. The present application optimizes the process conditions of yttrium-doped NFPP and combines the spray drying method to prepare a composite material precursor composed of nanoparticles, and then optimizes the high-temperature solid-phase sintering conditions to complete carbonization under an inert gas atmosphere. The obtained NFPP-Y composite positive electrode material has excellent electrochemical properties, which provides a new way for the low-cost development of high-performance sodium-ion battery positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The Na4Fe provided in Example 1 of the present application 2.9 Y 0.1 SEM image of (PO4)2(P2O7) cathode material;

[0013] Figure 2 SEM image of the Na4Fe3(PO4)2(P2O7) cathode material provided in Comparative Example 1 of the present application;

[0014] Figure 3 Na4Fe provided in Comparative Example 2 of this application 2.75 Y 0.25 SEM image of (PO4)2(P2O7) cathode material;

[0015] Figure 4 Na4Fe provided in Comparative Example 3 of this application 2.7 Y 0.3 SEM image of (PO4)2(P2O7) cathode material;

[0016] Figure 5 Na4Fe provided in Comparative Example 6 of this application 2.9 Y 0.1 SEM image of (PO4)2(P2O7) cathode material;

[0017] Figure 6 Na4Fe provided in Comparative Example 7 of this application 2.9 Y 0.1 SEM image of (PO4)2(P2O7) cathode material;

[0018] Figure 7 XRD diffraction patterns of the positive electrode materials provided in Example 1 of the present application and in Comparative Example 1;

[0019] Figure 8 This is a graph showing the first charge and discharge curves of the positive electrode materials provided in Example 1 and Comparative Examples 1-3 of the present application at a rate of 0.1C.

[0020] Fig. 9 This is a cycle performance diagram of the positive electrode material provided in Example 1 and Comparative Examples 1-3 of the present application at a 2C rate.

[0021] Fig.10 This is a rate performance diagram of 0.1-20C at a voltage of 2-4V for the positive electrode materials provided in Example 1 and Comparative Examples 1-3 of the present application. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0023] The present invention provides a method for preparing a composite positive electrode material, comprising the following steps:

[0024] According to the chemical formula Na4Fe3(PO4)2(P2O7), Na, Fe, PO4 3- and P2O7 4- The molar ratio of Na4P2O7, Fe(NO3)3·9H2O and NH4H2PO4 is respectively weighed, and yttrium salt and deionized water are added and uniformly mixed to obtain a mixed solution; the mixed solution is subjected to a grinding treatment and then spray-dried to form a dry powder precursor;

[0025] The powder precursor is ground and then heated to 500-580° C. at a heating rate of 2-5° C. / min in an inert gas atmosphere for sintering to obtain a composite positive electrode material.

[0026] Among them, Y 3+ With P2O7 4- The molar ratio is (0.05-0.2):1, preferably 0.1:1.

[0027] Wherein, the yttrium salt is one of Y(NO3)3, Y2(CO3)3, Y2(SO4)3 and YCl3, preferably Y2(CO3)3.

[0028] In a preferred embodiment of the present application, after the powder precursor is ground, it is heated to 500-580°C in an inert gas atmosphere at a heating rate of 2-5°C / min for sintering. In the step of obtaining a composite positive electrode material, the sintering conditions are preferably: heating to 580°C in an inert gas atmosphere at a heating rate of 2°C / min for sintering.

[0029] In a preferred embodiment of the present application, the mixed solution is ground to a particle size not greater than 100 nm.

[0030] Optionally, the step of grinding the mixed solution and then spray drying it to form a dry powder precursor comprises:

[0031] The mixed solution is ground and then spray-dried at an inlet temperature of 220-250° C. and an outlet temperature of 85-100° C. to form a dry powder precursor.

[0032] Optionally, the powder precursor is ground and then heated to 500-580° C. at a heating rate of 2-5° C. / min in an inert gas atmosphere for sintering to obtain a composite positive electrode material, comprising:

[0033] The powder precursor is ground, heated to 500-580°C at a heating rate of 2-5°C / min in an inert gas atmosphere for sintering, kept at this temperature for 10-15 hours, cooled naturally to room temperature, and ground to obtain a composite positive electrode material.

[0034] Optionally, the preparation method of the composite positive electrode material may specifically include the following steps: (1) according to the chemical formula of Na4Fe3(PO4)2(P2O7), Na, Fe, PO4 3- and P2O7 4- The molar ratio of Na4P2O7, Fe(NO3)3·9H2O and NH4H2PO4 were weighed respectively, and a certain amount of yttrium salt was added to make Y 3+ With P2O7 4-The molar ratio is in the range of 0.05-0.2, and the above raw materials are added to an appropriate amount of deionized water and mixed evenly by a magnetic stirrer. (2) The solution obtained in step (1) is transferred to a sand mill and ground for four hours to make the material particle size about 100 nanometers. (3) The mixed solution is spray dried at an inlet temperature of 220-250°C and an outlet temperature of 85-100°C to form a dry powder precursor. (4) After the powder precursor obtained in step (3) is fully ground with a mortar, it is placed in a tubular furnace and heated to 500-580°C at a heating rate of 2-5°C / min under an inert gas atmosphere, kept warm for 10-15 hours, then naturally cooled to room temperature, taken out of the furnace, and ground for 10 to 20 minutes to obtain NFPP-Y positive electrode material.

[0035] The amount of deionized water used can be adjusted by those skilled in the art based on the actual grinding conditions, and the amount has no effect on the properties of the obtained material.

[0036] The composite positive electrode material is described in detail with specific examples as follows. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are all commercially available unless otherwise specified.

[0037] Example 1

[0038] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.9:2:1:0.1. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2(CO3)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0039] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The mixture was carbonized at high temperature in a vacuum tube furnace by one-step calcination, that is, heated to 580°C at a heating rate of 2°C / min in an inert gas atmosphere and kept warm for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.9 Y 0.1 (PO4)2(P2O7) positive electrode material.

[0040] Example 2

[0041] Press Na+ :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.95:2:1:0.05. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2(CO3)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0042] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The Na4Fe was carbonized in a vacuum tube furnace by a one-step calcination method, that is, in an inert gas atmosphere, the temperature was increased to 580°C at a rate of 3°C / min and kept at this temperature for 10 hours, then naturally cooled to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.95 Y 0.05 (PO4)2(P2O7) positive electrode material.

[0043] Example 3

[0044] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.8:2:1:0.2. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2(SO4)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0045] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The mixture was carbonized at high temperature in a vacuum tube furnace by one-step calcination, that is, heated to 550°C at a heating rate of 5°C / min in an inert gas atmosphere and kept warm for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.8 Y 0.2 (PO4)2(P2O7) positive electrode material.

[0046] Example 4

[0047] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.9:2:1:0.1. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and YCl3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0048] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The Na4Fe was carbonized in a vacuum tube furnace by a one-step calcination method, that is, in an inert gas atmosphere, the temperature was increased to 550°C at a rate of 3°C / min and kept at this temperature for 10 hours, then naturally cooled to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.9 Y 0.1 (PO4)2(P2O7) positive electrode material.

[0049] Example 5

[0050] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.85:2:1:0.15. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y(NO3)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0051] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The Na4Fe was carbonized in a vacuum tube furnace by a one-step calcination method, that is, heated to 500°C at a heating rate of 2°C / min in an inert gas atmosphere and kept warm for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.85 Y 0.15 (PO4)2(P2O7) positive electrode material.

[0052] Example 6

[0053] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.95:2:1:0.05. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2(CO3)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0054] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The mixture was carbonized at high temperature in a vacuum tube furnace by one-step calcination, that is, heated to 500°C at a heating rate of 5°C / min in an inert gas atmosphere and kept at this temperature for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.95 Y 0.05 (PO4)2(P2O7) positive electrode material.

[0055] Comparative Example 1

[0056] Press Na + :Fe 3+ :PO3 3- :P2O7 4- Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.) and NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water in a molar ratio of 4:3:2:1, and mixed evenly with a magnetic stirrer.

[0057] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The mixture was carbonized at high temperature in a vacuum tube furnace by one-step calcination, that is, heated to 580°C at a heating rate of 2°C / min in an inert gas atmosphere and kept warm for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe3(PO4)2(P2O7) positive electrode material.

[0058] Comparative Example 2

[0059] Press Na + :Fe3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.75:2:1:0.25. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2(CO3)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0060] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The mixture was carbonized at high temperature in a vacuum tube furnace by one-step calcination, that is, heated to 580°C at a heating rate of 2°C / min in an inert gas atmosphere and kept warm for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.75 Y 0.25 (PO4)2(P2O7) positive electrode material.

[0061] Comparative Example 3

[0062] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.7:2:1:0.3. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2(CO3)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0063] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The mixture was carbonized at high temperature in a vacuum tube furnace by one-step calcination, that is, heated to 580°C at a heating rate of 2°C / min in an inert gas atmosphere and kept warm for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.7 Y 0.3 (PO4)2(P2O7) positive electrode material.

[0064] Comparative Example 4

[0065] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.9:2:1:0.1. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2O3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0066] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The mixture was carbonized at high temperature in a vacuum tube furnace by one-step calcination, that is, heated to 580°C at a heating rate of 2°C / min in an inert gas atmosphere and kept warm for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.9 Y 0.1 (PO4)2(P2O7) positive electrode material.

[0067] Comparative Example 5

[0068] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.9:2:1:0.1. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and YF3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0069] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The mixture was carbonized at high temperature in a vacuum tube furnace by one-step calcination, that is, heated to 580°C at a heating rate of 2°C / min in an inert gas atmosphere and kept warm for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.9 Y 0.1 (PO4)2(P2O7) positive electrode material.

[0070] Comparative Example 6

[0071] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.9:2:1:0.1. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y(HO)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0072] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The mixture was carbonized at high temperature in a vacuum tube furnace by one-step calcination, that is, heated to 580°C at a heating rate of 2°C / min in an inert gas atmosphere and kept warm for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.9 Y 0.1 (PO4)2(P2O7) positive electrode material.

[0073] Comparative Example 7

[0074] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.9:2:1:0.1. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2(CO3)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0075] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The mixture was carbonized at high temperature in a vacuum tube furnace by one-step calcination, that is, heated to 580°C at a heating rate of 1°C / min in an inert gas atmosphere and kept warm for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.9 Y 0.1 (PO4)2(P2O7) positive electrode material.

[0076] Comparative Example 8

[0077] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.9:2:1:0.1. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2(CO3)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0078] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The mixture was carbonized at high temperature in a vacuum tube furnace by one-step calcination, that is, heated to 580°C at a heating rate of 8°C / min in an inert gas atmosphere and kept warm for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.9 Y 0.1 (PO4)2(P2O7) positive electrode material.

[0079] Comparative Example 9

[0080] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.9:2:1:0.1. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2(CO3)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0081] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The mixture was carbonized at high temperature in a vacuum tube furnace by one-step calcination, that is, heated to 580°C at a heating rate of 10°C / min in an inert gas atmosphere and kept warm for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.9 Y 0.1 (PO4)2(P2O7) positive electrode material.

[0082] Comparative Example 10

[0083] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.9:2:1:0.1. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2(CO3)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0084] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The mixture was carbonized at high temperature in a vacuum tube furnace by one-step calcination, that is, in an inert gas atmosphere, the temperature was heated to 450°C at a heating rate of 2°C / min and kept at this temperature for 10 hours, then naturally cooled to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.9 Y 0.1 (PO4)2(P2O7) positive electrode material.

[0085] Comparative Example 11

[0086] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.9:2:1:0.1. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2(CO3)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0087] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The Na4Fe was carbonized in a vacuum tube furnace by a one-step calcination method, that is, heated to 480°C at a heating rate of 2°C / min in an inert gas atmosphere and kept warm for 10 hours, then cooled naturally to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.9 Y 0.1(PO4)2(P2O7) positive electrode material.

[0088] Comparative Example 12

[0089] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.9:2:1:0.1. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2(CO3)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0090] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The Na4Fe was carbonized in a vacuum tube furnace by a one-step calcination method, that is, in an inert gas atmosphere, the temperature was increased to 600°C at a rate of 2°C / min and kept at this temperature for 10 hours, then naturally cooled to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe 2.9 Y 0.1 (PO4)2(P2O7) positive electrode material.

[0091] Comparative Example 13

[0092] Press Na + :Fe 3+ :PO3 3- :P2O7 4- : Y 3- The molar ratio was 4:2.9:2:1:0.1. Na4P2O7 (analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.), Fe(NO3)3·9H2O (analytical grade, Xilong Scientific Co., Ltd.), NH4H2PO4 (analytical grade, Xilong Scientific Co., Ltd.) and Y2(CO3)3 (analytical grade, Shanghai Yien Chemical Technology Co., Ltd.) were weighed and dissolved in an appropriate amount of deionized water, and mixed evenly with a magnetic stirrer.

[0093] The above solution was transferred to a sand mill and ground for four hours. The mixed solution was spray dried at an inlet temperature of 220°C and an outlet temperature of 100°C to form a dry powder precursor. The Na4Fe was carbonized in a vacuum tube furnace by a one-step calcination method, that is, in an inert gas atmosphere, the temperature was heated to 650°C at a heating rate of 2°C / min and kept at this temperature for 10 hours, then naturally cooled to room temperature, removed from the furnace, and ground for 10 to 20 minutes to obtain Na4Fe2.9 Y 0.1 (PO4)2(P2O7) positive electrode material.

[0094] 0.2 g of the positive electrode material synthesized in the above Examples 1-6 and Comparative Examples 1-13, 0.025 g of the PVDF binder and 0.025 g of the Ketjen black conductive agent were weighed in a weight ratio of 8:1:1, and an appropriate amount of NMP solvent was added to make a slurry. The slurry was coated on aluminum foil, dried and cut into electrode discs, and assembled into CR2025 button batteries for electrochemical performance testing. The test results are shown in Table 1.

[0095] Table 1

[0096]

[0097]

[0098] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

[0099] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a composite positive electrode material, characterized in that: include: According to the chemical formula Na4Fe3(PO4)2(P2O7), Na, Fe, PO4 3- and P2O7 4- The molar ratio of Na4P2O7, Fe(NO3)3·9H2O and NH4H2PO4 were weighed respectively, and yttrium salt and deionized water were added and mixed uniformly to obtain a mixed solution; wherein Y 3+ With P2O7 4- The molar ratio is (0.05-0.2):1; the yttrium salt is one of Y(NO3)3, Y2(CO3)3, Y2(SO4)3 and YCl3; The mixed solution is ground and then spray-dried to form a dry powder precursor; The powder precursor is ground and then heated to 500-580° C. at a heating rate of 2-5° C. / min in an inert gas atmosphere for sintering to obtain a composite positive electrode material.

2. The method for preparing a composite positive electrode material according to claim 1, characterized in that: Y 3+ With P2O7 4- The molar ratio is 0.1:

1.

3. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The yttrium salt is Y2(CO3)3.

4. The method for preparing a composite positive electrode material according to claim 1, characterized in that: After the powder precursor is ground, it is heated to 500-580° C. at a heating rate of 2-5° C. / min in an inert gas atmosphere for sintering to obtain a composite positive electrode material, wherein the heating rate is 2° C. / min.

5. The method for preparing a composite positive electrode material according to claim 1, characterized in that: After the powder precursor is ground, it is heated to 500-580°C at a heating rate of 2-5°C / min in an inert gas atmosphere for sintering to obtain a composite positive electrode material, and the temperature is 580°C.

6. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The mixed solution is ground to a particle size not greater than 100 nm.

7. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The step of grinding the mixed solution and then spray drying it to form a dry powder precursor comprises: The mixed solution is ground and then spray-dried at an inlet temperature of 220-250° C. and an outlet temperature of 85-100° C. to form a dry powder precursor.

8. The method for preparing a composite positive electrode material according to claim 1, characterized in that: The powder precursor is ground and then heated to 500-580° C. at a heating rate of 2-5° C. / min in an inert gas atmosphere for sintering to obtain a composite positive electrode material, including: The powder precursor is ground, heated to 500-580°C at a heating rate of 2-5°C / min in an inert gas atmosphere for sintering, kept warm for 10-15 hours, cooled naturally to room temperature, and ground to obtain a composite positive electrode material.

9. A composite positive electrode material, characterized in that: The composite positive electrode material is prepared by the method for preparing the composite positive electrode material according to any one of claims 1-8.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the composite positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Porous composite biological material containing multiple active ions and preparation method thereof

    CN103520779A

  • Method for preparing Na4Fe3 (PO4) 2 (P2O7) by homogeneous phase method and application

    CN113060713A

  • Sodium ferric pyrophosphate sodium ion battery positive electrode material and preparation method thereof

    CN118047362A

  • Porous positive electrode material, preparation method thereof, positive electrode plate, secondary battery and electric equipment

    CN118431464A

  • Iron-based polyphosphate material with uniform mesoporous structure as well as preparation and application of iron-based polyphosphate material

    CN118561258A